ENGLISH ONLINE LEARNING AND CHALLENGES DURING THE COVID 19 PANDEMIC AT STMIK HANDAYANI MAKASSAR - Nurmadina HS Nurmadina HS; Yuliah Yuliah (English Education Journal, 2022)
The purpose of this study was to identify the problems experienced by students in the process of learning English during the pandemic and to describe the use of online learning media in the learning process. The formulation of the research problem is what problems are faced by STIMIK Handayani students in the online English learning process during the pandemic? And how is the application of online learning applications in the English learning process? This study uses a qualitative descriptive research approach. Respondents of this study were students who programmed English courses for the SK class with a total population of 12 people and were in the first semester. The total number of respondents is 6 students who are students who are actively participating in lectures. Questionnaires are used to explore information obtained from respondents later. The data analysis technique refers to Miles & Huberman through the stages of data collection, data reduction, data presentation, and drawing conclusions or verification. From the findings and discussion, the researcher concludes that the main obstacles commonly faced by students when participating in online learning are difficulties in understanding the material and poor signals. Other obstacles are in the form of feeling bored, less interactive, and having difficulty focusing. With this finding, the researcher hopes that there will be findings related to increasing the effectiveness of learning through online learning. Next is the application of application-based online learning. Based on the data collected and presented descriptively, the researcher concluded that the application of online learning was less effective.